A study of the influence of aggregate grading on concrete penetrability - Loseby, Michael John (Department of Civil Engineering, 2015)
Concrete is generally perceived as being an inherently durable material. However, many concrete structures need substantial repairs and maintenance during their service life, with the resultant costs to the economy reaching 3-5 % of GNP in some countries. Durability is therefore key in concrete design and specification. Aggregates constitute between 60 and 80 %, by volume, of typical concretes and have a profound influence on the physical properties of hardened concrete. The aggregate particle size distribution is usually selected so as to achieve a particle packing density that is equal to or near the maximum, which is seen as optimal for strength and durability. However, the influence of aggregate grading on durability apart from that which it has through its effect on particle packing density is not understood. Alternative mechanisms through which grading may effect durability include tortuosity and the porosity of the interfacial transition zone. This research aimed to determine the extent of the influence that aggregate grading has on concrete durability independently of particle packing density and to determine whether fineness modulus (FM) is a suitable and sufficient parameter for the characterisation of aggregate particle size distribution with regard to the performance based specification of concrete where durability is the concern. The coefficient of uniformity (Cu) and the use of gap or continuous grading were two further factors considered.